Exploring patterns of personal alarm system use and impacts on outcomes. (28th March 2021) - Andrew, Nadine E.; Wang, Yun; Teo, Ken; Callisaya, Michele L.; Moran, Christopher; Snowdon, David A.; Ellmers, Sonya; Beare, Richard; Richardson, Dean; Srikanth, Velandai
Abstract : Objectives: To describe the patterns of personal emergency response systems (PERS) use in a statewide cohort of older Australians. Methods: PERS data from clients enrolled in the Personal Alarm Victoria program between January 2014 and June 2017 were analysed. Alarm activation reasons were extracted, and a medical record audit was performed for a sub‐cohort of patients admitted to a local hospital following an alarm event. Descriptive statistics were used. Results: There were 42, 180 clients enrolled during the study (mean age 80 years, 80% female, 93% living alone). An ambulance attended 44% of the fall‐related events and 81% of events coded as unwell. Activation reasons were distributed equally between a fall and feeling unwell, and a repeating pattern of activation reasons was observed. In our sub‐cohort (n = 92), the majority of admissions (86%) followed an alarm activation coded as unwell. Conclusion: We demonstrated recurring patterns associated with the reasons for alarm use.